1986
DOI: 10.2307/1388942
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Family, and Adolescent Drug Use

Abstract: Using a national sample of over 17,000 high school seniors, we examined the effect of education of parents, employment status of mother, number of parents in household, religiosity, religious affiliation, gender, and race on alcohol and marijuana use. Contrary to some previous research, neither parental education nor employment status of mother was related to use of alcohol or marijuana. Adolescents who lived with both parents were less likely than adolescents in single-parent homes to use marijuana, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 24 publications
4
51
1
2
Order By: Relevance
“…(p. 71) For alcohol, the difference between active and inactive members was almost twice as great for Church of Jesus Christ of the Latter-Day Saints members compared with fundamentalist Protestants. For marijuana, Church of Jesus Christ of the Latter-Day Saints members again had the greatest difference, followed by Jews (Amoateng & Bahr, 1986). …”
Section: Religiosity and Religious Affiliationmentioning
confidence: 99%
See 3 more Smart Citations
“…(p. 71) For alcohol, the difference between active and inactive members was almost twice as great for Church of Jesus Christ of the Latter-Day Saints members compared with fundamentalist Protestants. For marijuana, Church of Jesus Christ of the Latter-Day Saints members again had the greatest difference, followed by Jews (Amoateng & Bahr, 1986). …”
Section: Religiosity and Religious Affiliationmentioning
confidence: 99%
“…It can protect adolescents against substance use in a number of ways. It may inhibit adolescent risk behavior by altering behavior-influencing values or by functioning as an external control factor (Amoateng & Bahr, 1986). Some religions explicitly prohibit substance use.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] A national survey by the Gallup Poll found that 95% of teenagers believe in God, 93% believe that God loves them, 80% say that their religious beliefs are very or fairly important to them, and 52% have attended a religious service in the past month. 8 Miller et al 9 found that religiousness had twice the negative strength of association with substance dependence among adolescents compared with adults.…”
Section: Introductionmentioning
confidence: 99%